Pendampingan Manajemen Penyediaan Hijauan Pakan Ternak Kambing Di Desa Saribaye Kecamatan Lingsar - Sukarne; Harjono; Oscar Yanurianto; Syalsa Bella Fitriana; Yusuf Akhyar Sutaryono (Universitas Mataram, 2026)
This community service program aimed to support goat farmers in Saribaye Village, Lingsar District, in improving livestock production through more efficient and sustainable feed management. At present, farmers in Saribaye Village still depend on natural forage available in the surrounding area, the availability of which is limited, especially during the dry season. This condition results in nutritional problems in livestock and leads to decreased meat and milk productivity. The program provided training and assistance on feed processing and preservation techniques, including silage production, fermented feed preparation, and the utilization of agricultural waste as ingredients for complete feed. The approach applied in this program focused on simple, low-cost, and applicable technologies using locally available materials in Saribaye Village. Through this activity, farmers are expected to be able to manage livestock feed more independently and sustainably, particularly in anticipating feed shortages during the dry season. The community service activities were conducted in two stages: a preparation stage and an implementation stage. The preparation stage involved coordination and the formulation of an activity plan, while the implementation stage included lectures, demonstrations, and extension activities. The materials delivered covered feeding strategies, complete feed formulation techniques, and agricultural waste-based feed processing. This program is expected to improve farmers’ capacity in managing livestock enterprises more effectively and ultimately enhance the welfare of goat farmers in Saribaye Village.